Study of the protective effect of ischemic and pharmacological preconditioning on hepatic ischemic reperfusion injury induced in rats - Osman, Afaf S (JGH Open, 2017)
BACKGROUND AND AIM: Hepatic ischemia reperfusion injury is the main cause of liver failure following liver surgery, so an effective method is needed to prevent or reduce this hepatic injury. The aim of the present study is to investigate the potential effect of ischemic preconditioning versus pharmacological preconditioning with lisinopril or verapamil for protection against hepatic ischemia reperfusion injury induced in rats. METHODS: Rats were divided into six groups. Group I served as control untreated. Rats of group II were subjected to laparotomy without induction of ischemia reperfusion. Ischemia reperfusion by ligation of the portal trait for 30 min, followed by reperfusion for 2 h, was performed in rats of groups III–VI. Ischemic preconditioning was performed for rats of group IV before induction of ischemia reperfusion. Lisinopril and verapamil was given daily for 3 days before induction of ischemia reperfusion in groups V and VI, respectively. Serum level of liver transaminases and liver malondialdehyde content were measured, and hepatic histopathological examination was assessed. RESULTS: Induction of ischemia reperfusion resulted in significant elevation of liver transaminases and liver malondialdehyde content associated with significant hepatic histopathological injury that were significantly improved by ischemic preconditioning, lisinopril, or verapamil treatment. Verapamil showed the most significant improvement compared with ischemic preconditioning or lisinopril treatment. CONCLUSION: Ischemic preconditioning and pharmacological preconditioning by lisinopril or verapamil can protect against hepatic ischemia reperfusion probably through inhibition of oxidative stress and neutrophil infiltration. The most potent protection is demonstrated by verapamil treatment.